The Cutch Desert Immobilization Scheme - Joshi, N. J. (Indian Forester, 1959)
The article deals with the scheme for the immobilization of the Cutch Desert, sanctioned by the Government of Bombay under the Second Five-Year Plan. The situation and the locality factors of the area bordering the desert are given. The nature of the problem is explained. The details of the Scheme and the work actually executed so far are given. Lastly, an assessment of the results achieved is made and experiences gained are metioned.